(untitled) - N. Gregory Mankiw; N. Gregory Mankiw (Fort Worth, 2007)
More of this book is devoted to applcations and less to formal economic theory than is the case studies illustrating how the principles course. Most chapters include case studies illustrating how the principles of economics are applied
Keywords: Macroeconomics